Optimal breast cancer pathology manifesto. Issue 16 (November 2015) - Tot, T.; Viale, G.; Rutgers, E.; Bergsten-Nordström, E.; Costa, A.
<x xml:space="preserve">Abstract</x> Highlights This manifesto calls for high quality pathology services for all breast cancer patients in Europe. The pathology services must meet the needs of the patients and clinicians. The diagnostic and prognostic information for decision making must be timely delivered. Hospitals should ensure pathology integrated in multidisciplinary teamwork visible to patients. Pathology: vital discipline with substantial career potential for pathologists and technicians.